Design of Student Attendance User Interface using Figma at SMA Negeri 1 Sukamakmur Aceh Besar - Zikri, Ikhsan Nul; Imilda (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
This research focuses on developing an attractive, valid, practical, and effective information system based on Android applications. The primary target users are eleventh and twelfth-grade students at SMA Negeri 1 Sukamakmur who will participate in industrial work practice programs. The application features facilitate communication between industrial work practice students, teachers, and industry supervisors. These features enhance the quality and effectiveness of industrial work practice programs while creating consistent synergy between schools and industry partners. The study employs Research and Development (R&D) methodology with a waterfall development model or linear sequential model. Data collection was supported through field observations and interviews with school stakeholders, including teachers, students, and industry department heads. This methodology provided valid data for application development by identifying strengths, weaknesses, opportunities, and threats in creating the Prakerin.com application. Student questionnaires were used as research instruments, and Flutter was utilized as the development platform. The research aims to create an Android-based industrial work practice information system that is attractive, valid, practical, and effective. Additionally, it seeks to facilitate teacher-student communication during industrial work practice implementation to support optimal assessment results and enhance student competency development.